THE INFLUENCE OF LIQUIDITY AND PROFITABILITY ON FIRM VALUE WITH CORPORATE SOCIAL RESPONSIBILITY (CSR) AS A MEDIATION VARIABLE (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2022)
This study aims to determine the effect of liquidity and profitability on firm value through CSR. Liquidity is measured using the current ratio, profitability with return on assets, firm value with the price to book value, and CSR with GRI-G4 standards. This research was conducted on manufacturing companies listed on the Stock Exchange with a population of 163 companies using the purposive sampling technique to produce 66 companies. These studies turned into performed the use of the Smart-PLS software. Based on the evaluation and speculation trying out results, it is able to be concluded that liquidity has a terrible and insignificant impact on company cost. Liquidity has a terrible and insignificant impact on company costs. Profitability has an advantageous and extensive impact on company costs. Profitability has an advantageous and extensive impact on company costs. Profitability has an advantageous and extensive effect on CSR. CSR has advantages however now no longer extensive impact on company costs. CSR can not mediate the connection between liquidity to company cost and profitability to company cost. Keywords: Liquidity, Profitability, Corporate Social Responsibility, Firm Value